Perception of trust as a mediation variable on the influence of perception of ease and perception of usefulness in interest in using Gopay - A. Sudrajat; Agtovia Frimayasa (Sean Institute, 2024)
This research aims to investigate the influence of perceived convenience, perceived usefulness, and perceived trust on interest in using GoPay. This research uses a simple random sample, where each member of the GoPay user population has the same opportunity to be selected as a research respondent. Sampling is carried out randomly without paying attention to specific characteristics or attributes of the population. The sample used in this research was 100 respondents. Data analysis was done using the Partial Least Square (PLS) method using SmartPLS version 3 software. The results of the study show that perceived convenience, perceived usefulness, and perceived trust have a significant influence on interest in using GoPay. Users with ease of use, high usability, and high confidence in the GoPay system are more interested in using the service.